Beyond Play: Researching the Transformative Power of Digital Gaming in Deeply Mediatized Societies - Christian Schwarzenegger; Erik Koenen; Kerstin Radde-Antweiler; Karsten D. Wolf (Media and Communication)
Digital gaming has evolved from a peripheral activity to a central aspect of mediatized lifeworlds, significantly impacting media culture and society. Despite its pervasive influence, digital gaming research often occupies a marginalized status within broader academic disciplines. This article advocates for recognizing digital gaming as an integral part of the media landscape and understanding its role within a deeply mediatized society. By adopting a holistic perspective, this study emphasizes the interconnectedness of digital gaming with other media forms and cultural practices, highlighting its significance in driving digital transformation. Therefore, we argue for a dual development: one that removes gaming from its segregated special status and recognizes it as an integral part of the media landscape, and another that situates the unique aspects of gaming within the broader context of a society deeply transformed and shaped by media; capturing both its significance and its role as part of the whole. We elaborate on the concept of gamevironments bridging deep mediatization research and communicative figurations to comprehend change brought about by the transformative power of digital gaming in deeply mediatized societies. Gamevironments encompass transmedia figurations and narratives, cross-media adaptations, social interactions, user-generated content, and the cultural and educational impacts of gaming. We discuss the analytical potential of gamevironments along five distinct yet interrelated areas (making of gamevironments, values in and of gamevironments, governance of gamevironments, education in and for gamevironments, and researching gamevironments) to provide a comprehensive view of digital gaming’s transformative impact on digital society.